2017
DOI: 10.1186/s40413-017-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone allergy: clinical aspects, causes and therapeutic strategies – Update and secondary publication

Abstract: Sex hormone allergy as a clinical syndrome has been known for almost a century. Due to the diversity of clinical presentation regarding symptoms and disease patterns, the optimal patient care represents an enormous interdisciplinary challenge. Frequently, hypersensitivity reactions affect more than one sex hormone and double positive tests for estrogen and progesterone have been described. Since the menstrual cycle dependent symptoms range from skin afflictions, gynecological problems to non-specific reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Whereas, the male recorded 23.3% ,42.9% and 15.4 % respectively. These results agreed with Yao et al, [13], who reported an increase of hypersensitivity with increasing age due to total immunoglobulin E levels increased with age until 14-15 years, and declined thereafter. In addition, elevated of the Body Mass Index (BMI) was associated with greater prevalence of wheezing and eczema.…”
Section: Resultssupporting
confidence: 93%
“…Whereas, the male recorded 23.3% ,42.9% and 15.4 % respectively. These results agreed with Yao et al, [13], who reported an increase of hypersensitivity with increasing age due to total immunoglobulin E levels increased with age until 14-15 years, and declined thereafter. In addition, elevated of the Body Mass Index (BMI) was associated with greater prevalence of wheezing and eczema.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, induction of tolerance via intradermal application with naive or bioidentical sex hormones could be used to inhibit cell-mediated immune responses, as we found in PMS, and animal model of recurrent abortions,15, 16, 17, 18, 19 or even in a broader spectrum of autoinflammatory diseases 20 …”
Section: Discussionmentioning
confidence: 94%
“…During the 2 year period starting on April 14 , 2009 to April 13 , 2011, 35 subjects have been enrolled in the study (Table 1). Twenty 20 subjects (57%) dropped out of the study due to various personal reasons and screening failures such as hepatitis, willingness to use contraceptives, a long trip, operation etc., but more interestingly due to resolution of symptoms during the skin test phase and lack of incentive to continue their participation.…”
Section: Resultsmentioning
confidence: 99%
“…Patients already diagnosed with progesterone hypersensitivity benefit from more information and better surveillance during pregnancy while asymptomatic women might manifest atypical symptoms. For example, unrevealing workup for habitual idiopathic pregnancy losses showed immediate hypersensitivity towards estrogen and progesterone in 50% of patients and delayed hypersensitivity in 70% of patients (13). Even though most women demonstrated combined hypersensitivity, some had only estrogen or progesterone hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%